Exploring the Causes and Physical Manifestations of Glossophobia among University Students - Peter Babajide Oloba; Andani Tshidzumba; Lineo Nkabane-Sekopo (STAI Miftahul Ula Nganjuk, 2025)
This study investigates the causes and physical manifestations of glossophobia among university students, with a focus on the University of Johannesburg. The aim is to identify the underlying causes of glossophobia and explore its physical symptoms in students. Adopting a qualitative research design within a constructivist paradigm, the study uses a phenomenological approach to capture the lived experiences of students. Ten participants with self-reported glossophobia were selected through purposive sampling, and data were collected via semi-structured interviews. The data were analyzed using qualitative content analysis. The results indicate that glossophobia is primarily triggered by factors such as inadequate preparation, fear of judgment, fear of failure, perfectionism, and xenoglossophobia. These factors lead to physical symptoms, including hand shaking, voice trembling, increased heart rate, sweating, and shortness of breath, which significantly impair students' public speaking abilities. Based on these findings, the study recommends several interventions to mitigate glossophobia, such as organizing public speaking workshops, creating peer support networks, promoting relaxation and mindfulness techniques, encouraging gradual exposure to public speaking, offering professional counseling, and raising awareness about glossophobia and mental health. These measures aim to alleviate anxiety, boost confidence, and create a supportive environment for students. Addressing glossophobia can enhance students' academic experiences, improve communication skills, and promote overall well-being.